Existence Of The Towani Tolotang Community Based On Atr Candy Number 18 Of 2019 - Heri Heril; Andi Suriyaman M Pide; Sri Susyanti Nur (LEGAL BRIEF, 2022)
The Towani Tolotang community has for generations passed on and maintained the culture and beliefs that originated from its ancestors. The passage of time is quite long, proving that their community is able to survive all the influences and penetrations of other cultures that surround from all timelines. The purpose of this study is to determine the existence of the Towani Tolotang community based on the ATR Regulation Number 18 of 2019. This research is an empirical legal research, with primary and secondary data sources and analyzed descriptively. The results of the study concluded that the Towani Tolotang community cannot be said to be an indigenous law community, because of the non-fulfillment of the creteria listed in article 2 paragraph 2, Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 18 of 2019. Such as not having controlled indigenous territories and clear customary institutions. However, the Towani Tolotang community can be said to be an ordinary indigenous people, where they still have communally controlled areas that are only used as religious activities and traditional ceremonies and have Uwa' and Uwatta as the traditional stakeholders who are the highest decision-making among them.